Analisis Sifat Putusan Dewan Kehormatan Penyelenggara Pemilu terhadap Perwujudan Good Governance Ditinjau dari Perspektif Profesionalisme Birokrasi dan Pelayanan Publik - Christilla, Maura Ovi Yudha; Isharyanto, Isharyanto (Res Publica: Jurnal Hukum Kebijakan Publik, 2021)
ABSTRACTThis thesis aims to analyze the correlation of Honorary Board of Organizer (DKPP) of elections’s verdict, which is final and binding with good governance embodiment by professionalism’s perspective of bureaucracy and public service and identify implication of DKPP’s verdict toward good governance embodiment. The type of this research is normative legal research which has descriptive method. Based on author’s research results show that the DKPP’s verdict is point out the correlation with good governance implementation by the concept of good governance include of principles and purpose of good governance and institute professionalism concept include of professionalism characteristics of institute. Implication of DKPP’s verdict defined that there are actualization for the purpose and principle of general election, manifesting of good governance objective, and fulfillment of bureaucracy and public service indicators that give priority to public service principles.Keywords: the verdict of DKPP; institute professionalism; bureaucracy and public service; good governance.